2022
DOI: 10.1002/cyto.b.22106
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of monocyte gating to quantify monocyte subsets for the diagnosis of chronic myelomonocytic leukemia

Abstract: BackgroundThe presence of >94% classical monocytes (MO1, CD14++/CD16‐) in peripheral blood (PB) has an excellent performance for the diagnosis of chronic myelomonocytic leukemia (CMML). However, the monocyte gating strategy is not well defined. The objective of the study was to compare monocyte gating strategies and propose an optimal one.MethodsThis is a prospective, single center study assessing monocyte subsets in PB. First, we compared monocyte subsets using 13 monocyte gating strategies in 10 samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…These results were first confirmed by a single center study from Eric Padron's team, which reported a 86% specificity and 100% sensitivity based on 29 CMML patients (Talati et al, 2017). Three other studies highlighted the high specificity of the 94% cMo cut‐off, from 94% to 95% (Hudson et al, 2018; Jurado et al, 2023; Pophali et al, 2019), yet with lower sensitivity, 88% based on 16 CMML cases (Hudson et al, 2018) and 75% based on 43 CMML cases (Pophali et al, 2019). A French oligocenter study using data from real life conditions also confirmed the good performances obtained with the 94% threshold, with a specificity of 89.7% and a sensitivity of 93.6% with 47 CMML patients included (Tarfi et al, 2018).…”
Section: Part 2: Interpretation Recommendations Of Circulating Monocy...mentioning
confidence: 99%
See 3 more Smart Citations
“…These results were first confirmed by a single center study from Eric Padron's team, which reported a 86% specificity and 100% sensitivity based on 29 CMML patients (Talati et al, 2017). Three other studies highlighted the high specificity of the 94% cMo cut‐off, from 94% to 95% (Hudson et al, 2018; Jurado et al, 2023; Pophali et al, 2019), yet with lower sensitivity, 88% based on 16 CMML cases (Hudson et al, 2018) and 75% based on 43 CMML cases (Pophali et al, 2019). A French oligocenter study using data from real life conditions also confirmed the good performances obtained with the 94% threshold, with a specificity of 89.7% and a sensitivity of 93.6% with 47 CMML patients included (Tarfi et al, 2018).…”
Section: Part 2: Interpretation Recommendations Of Circulating Monocy...mentioning
confidence: 99%
“…Abnormal partitioning of peripheral blood monocyte subset is now recognized as an essential tool for the screening of monocytosis in order to distinguish CMML from reactive monocytosis (Khoury et al, 2022) (Talati et al, 2017). Three other studies highlighted the high specificity of the 94% cMo cut-off, from 94% to 95% (Hudson et al, 2018;Jurado et al, 2023;Pophali et al, 2019), yet with lower sensitivity, 88% based on 16 CMML cases (Hudson et al, 2018) and 75% based on 43 CMML cases (Pophali et al, 2019).…”
Section: Interpretation Recommendations Of Circulating Monocyte Parti...mentioning
confidence: 99%
See 2 more Smart Citations
“…The last article in this issue, Jurado et al focused on optimizing the monocyte gating strategy for diagnosing chronic myelomonocytic leukemia (CMML). They proposed a 10‐color tube and computational analysis to improve the reproducibility of monocyte subset quantification (Jurado et al, 2022). Further studies highlight the robustness of the “monocyte assay” for CMML diagnosis, the complexities in distinguishing CMML from blastic plasmacytoid dendritic cell neoplasm (BPDCN), and the potential of immunophenotypic analysis in differentiating CMML from reactive monocytosis (Espasa et al, 2021; Feng et al, 2018; Wagner‐Ballon et al, 2023).…”
mentioning
confidence: 99%